2002
DOI: 10.1128/iai.70.1.192-198.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inflammation, Organ Damage, and Oxidant Stress Induced by Salmonella enterica Serovar Muenchen Flagellin and Serovar Enteritidis Lipopolysaccharide

Abstract: Gram-negative sepsis is related to the activation of interconnected inflammatory cascades in response to bacteria and their products. Recent work showed that flagellin, the monomeric subunit of bacterial flagella, triggers innate immune responses mediated by Toll-like receptor 5. Here, we compared the effects of Salmonella enterica serovar Enteritidis lipopolysaccharide (LPS) and recombinant Salmonella enterica serovar Muenchen flagellin administered intravenously (100 g) to mice. Flagellin and LPS both elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 32 publications
8
61
0
Order By: Relevance
“…21 The flagellin-TLR5 axis might also trigger cardiac innate immune responses and result in cardiovascular dysfunction. 22 Consistent with previous reports, 23,24 we previously demonstrated that either intranasally or intraperitoneally administered flagellin could induce a significant increase in the serum aminotransferase levels in mice, 25 suggesting that flagellin might be a potent inducer of liver damage. Flagellin-triggered responses exert various effects on different cells, tissues and organs; these responses vary greatly according to the dose, physiological condition of the cell, the animal used and the experimental setting.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…21 The flagellin-TLR5 axis might also trigger cardiac innate immune responses and result in cardiovascular dysfunction. 22 Consistent with previous reports, 23,24 we previously demonstrated that either intranasally or intraperitoneally administered flagellin could induce a significant increase in the serum aminotransferase levels in mice, 25 suggesting that flagellin might be a potent inducer of liver damage. Flagellin-triggered responses exert various effects on different cells, tissues and organs; these responses vary greatly according to the dose, physiological condition of the cell, the animal used and the experimental setting.…”
Section: Introductionsupporting
confidence: 77%
“…High-dose flagellin induced acute liver function abnormality, damage and oxidative stress As reported previously, 23,24 flagellin induced widespread systemic inflammation and significant increase in aminotransferase…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…We and others have shown that i.v. injection of flagellins promotes a systemic response, characterized by the production of proinflammatory mediators (such as TNF-␣ or IL-6) and DC activation (5,6,(13)(14)(15)(16)(17). Furthermore, flagellins trigger mucosa-specific innate and adaptive defense mechanisms (18 -20).…”
Section: Deletion Of Flagellin's Hypervariable Region Abrogates Antibmentioning
confidence: 99%